2016
DOI: 10.1186/s12944-016-0289-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal sodium butyrate supplement elevates the lipolysis in adipose tissue and leads to lipid accumulation in offspring liver of weaning-age rats

Abstract: Background: Sodium butyrate (SB) is reported to regulate lipid metabolism in mammals, and the relationship between maternal nutrition and offspring growth has drawn much attention in the last several years. Methods: To elucidate the effects of maternal dietary SB supplementation on hepatic lipid metabolism in weaning rats, we fed 16 primiparous purebred female SD rats either a chow-diet or a 1 % sodium butyrate diet throughout pregnancy and lactation. At weaning age, samples of the maternal subcutaneous adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Body weight of dams showed no significant difference between the butyrate group and the control group (28) . Maternal butyrate supplementation demonstrated a trend towards increasing litter weight, litter size (28) and the ratio of muscle weight:body weight (7路27 (SE 0路16) v. 6路79 (SE 0路19) g, P < 0路1) as well as enhanced muscle weight of the offspring (0路54 (SE 0路01) v. 0路48 (SE 0路02) g, P < 0路05) compared with the control group. The average weight of newborns (7路04 (SE 0路14) v. 7路18 (SE 0路12) g, P > 0路05) and the body weight of weaning rats (28) showed no significant differences between the two groups.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Body weight of dams showed no significant difference between the butyrate group and the control group (28) . Maternal butyrate supplementation demonstrated a trend towards increasing litter weight, litter size (28) and the ratio of muscle weight:body weight (7路27 (SE 0路16) v. 6路79 (SE 0路19) g, P < 0路1) as well as enhanced muscle weight of the offspring (0路54 (SE 0路01) v. 0路48 (SE 0路02) g, P < 0路05) compared with the control group. The average weight of newborns (7路04 (SE 0路14) v. 7路18 (SE 0路12) g, P > 0路05) and the body weight of weaning rats (28) showed no significant differences between the two groups.…”
Section: Resultsmentioning
confidence: 78%
“…1(a)). Our previous study has been reported that serum concentrations of total cholesterol and TGA in dams and weaned offspring did not change with butyrate supplementation (28) .…”
Section: Resultsmentioning
confidence: 79%
“…; Morrison & Preston ; Zhou et al . ). However, such information is lacking aquatic animals and yet to be explored.…”
Section: Conclusion and Perspectivementioning
confidence: 97%
“…Furthermore, there is currently limited information on the SCFAs receptors and the routes by which SCFAs positively or negatively influence metabolic functioning in aquatic animals. SCFAs elicit their beneficial effects by controlling the levels of fatty acid oxidation and fat storage in multiple tissues, as well as, regulating glucose homoeostasis in human and mice (den Besten et al 2013;Canfora et al 2015;Morrison & Preston 2016;Zhou et al 2016). However, such information is lacking aquatic animals and yet to be explored.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Butyrate belongs to SCFAs and is an important gut microbial metabolite derived from fermentation of nondigestible polysaccharides. Butyrate has been demonstrated with critical role in affecting metabolic diseases development through a variety of ways including modulation of energy harvest, hepatic lipogenesis and gluconeogenesis, adipokine signaling in adipocytes, intestinal permeability and appetite regulation in brain [145,146]. Research showed that administration of sodium butyrate alleviated inflammation and fat accumulation in HFD-induced NAFLD mice by increasing the abundances of the beneficial bacteria Christensenellaceae, Blautia and Lactobacillus [147].…”
Section: Gut Microbiota-targeted Therapies With Other Approachesmentioning
confidence: 99%